THE EFFECT OF SALES VOLUME, SELLING PRICE, AND NUMBER OF TYPES OF INTEREST ON THE INCOME OF CUT FLOWER STALL TRADERSAT RAWA BELONG FLOWER MARKET, WEST JAKARTA - Achmad Tjachja Nugraha; Agustina Senjayani; Nur Huriyandah (Syarif Hidayatullah State Islamic University Jakarta, 2020)
Horticultural crops, especially cut flowers, are a very distinctive commodity, where entrepreneurs are required to pay special attention to their business. The high demand for cut flowers under certain conditions that are not accompanied by the amount of cut interest supply available in the market, results in fluctuations in sales volume and selling prices of cut flowers and has an impact on the income of flower traders from the sale of cut flowers. The purpose of this study is to determine the characteristics of merchants and the size of sales volume, selling price, number of types of flowers, and income of cut flower stall traders; to analyze the effect of sales volume, selling price and amount of interest on the income of cut flower stall traders; and to analyze the sensitivity of the amount of interest type to the income of the vendor of the cut flower stall.This study was conducted at the Rawa Belong Flower Market with a population of 59 cut flower stall vendors, and the sample used was 37 vendors. Sampling using Simple Random Sampling technique. The data analysis method uses multiple regression with the help of SPSS 20 Software.From the results of data processing using SPSS 20 obtained the regression equation Y= -57220431.407 + 7105.565X1 + 1341.385X2 - 2428398.684X3 with tcount on sales volume = 16.164 > ttable (2.032) so that the reject Ho1; t count at the selling price = 5.806 > ttable (2.032) so that the reject Ho2; and t count on the number of types of interest = -2.868 > ttable (-2.032) so that it accepts Ho3; while Fcount (457.812) > Ftable (2.89) so reject Ho4. The correlation coefficient is worth 0.988 and the coefficient of determination is worth 0.974 which means that the sales volume, selling price, and the number of types of interest have a strong influence on the income of stall traders. Based on the value of the sensitivity of the number of types of interest to the income of stall traders obtained an elasticity value of -0.262 (inelastic).